Efficacy of alternate mucosa–submucosa clip closure in preventing postoperative adverse events for patients with gastric mucosal lesions after endoscopic submucosal dissection: a multicenter retrospective study - Lu Chen; Jingjing Jiang; Hongxia Li; Xin Yin; Xiajiao Tang; Yinnan Zhu; Wei Chen; Qin Lu; Ruihua Shi (Therapeutic Advances in Gastroenterology)
Background: Endoscopic submucosal dissection (ESD) is the first-line treatment for gastric mucosal lesions. The artificial ulcers caused by ESD can lead to bleeding, perforation, and other adverse events. Objectives: This study aimed to evaluate the efficacy of alternate mucosa–submucosa clip in preventing adverse events following ESD for gastric mucosal lesions. Design: Multicenter retrospective observational study. Methods: Data from 924 patients who underwent ESD for gastric mucosal lesions were retrospectively collected and categorized into completely closed and unclosed groups based on postoperative wound management. The incidence of adverse events and postoperative wound healing rate at 1 and 3 months were compared between the groups, and the factors related to delayed bleeding after ESD were analyzed. Results: The rate of delayed hemorrhage was lower in the completely closed group than in the unclosed group (0.8% vs 7.6%; p  < 0.001), and subgroup analysis showed that this effect was consistent across all subgroups. The postoperative abdominal pain score was lower in the completely closed group than in the unclosed group (0 vs 2, p  < 0.001). One month postoperatively, the wound healing rate was higher in the completely closed group (77.6% vs 55.1%; p  < 0.001). Multivariable analysis showed that the presence of ulcers or scars on the lesion surface, and lesions located in the lower one-third of the stomach were risk factors for postoperative bleeding. Conclusion: Application of alternate mucosa–submucosa clip closing the wound of ESD reduced the risk of postoperative bleeding, alleviated postoperative abdominal pain, and promoted artificial wound healing.